2018
DOI: 10.1653/024.101.0419
|View full text |Cite
|
Sign up to set email alerts
|

Resistance in Rice to Tibraca limbativentris (Hemiptera: Pentatomidae) Influenced by Plant Silicon Content

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…Silicon fertilization increases the silicon content and chlorophyll content of plants, in consequence, the resistance of rice plants, either it was sprayed on the plants or applied on the soil. Si treatment increases the chlorophyll content of plants resulted in lower percentage of damaged stems in the rice cultivars [160].…”
Section: Pest Resistancementioning
confidence: 96%
“…Silicon fertilization increases the silicon content and chlorophyll content of plants, in consequence, the resistance of rice plants, either it was sprayed on the plants or applied on the soil. Si treatment increases the chlorophyll content of plants resulted in lower percentage of damaged stems in the rice cultivars [160].…”
Section: Pest Resistancementioning
confidence: 96%
“…Our observation of reduced fitness in planthoppers adds to observations of soil silicon effects across a range of rice pests (e.g., Tibraca limbativentris [ 60 ]; leaffolders [ 62 , 72 , 83 , 84 ]; stemborers [ 33 , 39 , 40 , 64 , 85 ]; rice water weevil— Lissorhoptrus oryzophilus [ 28 ]; and golden apple snail— Pomacea canaliculata [ 66 ]). Although research has mainly been conducted under controlled conditions, a few studies indicate that these effects can also be observed in rice fields [ 15 , 28 , 30 , 86 ].…”
Section: Discussionmentioning
confidence: 65%
“…We did not analyze any varieties other than IR22 in our experiments. The capacity to assimilate silicon differs between varieties, but this has not been consistently related to pest resistance or susceptibility where plants possess major resistance genes [ 39 , 40 , 60 ]. Soil amendments that contain high amounts of silicon have also been associated with increasing rice seedling weight [ 61 , 62 , 63 ], higher C:N ratios in leaf tissues [ 57 , 63 ], higher sugar and protein contents [ 57 ], and higher chlorophyll contents [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to S. frugiperda in rice genotypes has been little studied in Brazil. Some studies on rice and S. frugiperda have examined the induction response to silicon and its negative effects on insect biology (Nascimento et al, 2017;França et al, 2018). Other studies have looked at creating resistance to S. frugiperda by inserting Bacillus thuringiensis (cry1Aa and cry1B) in rice (Pinto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Screening of resistant rice genotypes has become an important component of IPM. Nevertheless, pest resistance in the rice genotypes of Brazil is limited and has only been identified for the stalk borer Diatraea saccharalis Fabricius (Lepidoptera: Crambidae) and rice stalk stink bug Tibraca limbaventris Stål (Hemiptera: Pentatomidae) (Nascimento and Barrigossi, 2014;Nascimento et al, 2015;Correa et al, 2018;França et al, 2018;Almeida et al, 2020). There are currently no rice genotypes that are characterized as resistant to S. frugiperda.…”
Section: Introductionmentioning
confidence: 99%